Revisiting the Uppsala model from a history-to-theory perspective: New lessons on network positioning from a global electric company - Silva, Alvaro Ferreira; Gomes, Emanuel; Vendrell-Herrero, Ferran; Lehman, David W. (Palgrave Macmillan, 2026)
A firm cannot internationalize on its own. Rather, a network of multiple firms is critical. Accordingly, the Uppsala model has been reformulated in recent years to account for the role of networks in the firm internationalization process. Still unclear, however, is how a firm’s network position evolves—both within individual foreign market entries and across successive entries—under changing firm, industry, and macro conditions. This study utilizes the historical case method to address this gap. Specifically, it examines the birth, rise, and global dominance of Sofina, a Belgian electric company, as it entered various foreign markets from the turn of the 20th century until the start of the Second World War. Our analysis highlights network positioning as a dynamic process that unfolds both within and across market entries. Importantly, these processes are facilitated by ongoing firm commitments of financial, managerial, and physical resources, and are linked to different sources of organizational learning. They are also shaped by global events as well as firm- and industry-level factors. The explanatory model that emerges from this analysis suggests that firms may need to be more agile than previously acknowledged by continuously repositioning themselves within networks to successfully expand their global footprints.
Keywords: Business history; Business networks; Electricity industry; Organizational learning; Projects; Uppsala model of internationalization; fi=Strateginen johtaminen|en=Strategic Management|